ChemInform Abstract: Novel Properties and Potential Applications of Functional Ligand‐Modified Polyoxotitanate Cages. Issue 45 (October 2016) - Li, Ning; Matthews, Peter D.; Luo, He‐Kuan; Wright, Dominic S.
Abstract: Review: 72 refs.